Digital Leadership in Improving Digital Financial Literacy and Sustainability of Cooperative Business at Tri Capital Investama Service Cooperative - Purnamasari, Dewi (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study investigates the influence of digital financial leadership, digital leadership experience, and digital leadership vision on digital financial literacy and the sustainability of cooperative businesses. Employing a quantitative approach, data were collected from cooperative members in Central Java through structured questionnaires. The analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among the variables. The findings reveal that digital financial leadership, along with leadership experience and vision, significantly enhances digital financial literacy. Furthermore, digital financial literacy mediates the relationship between leadership variables and the sustainability of cooperative businesses. These results underscore the pivotal role of digital leadership in fostering financial literacy, which in turn contributes to the long-term sustainability of cooperatives. The study highlights the necessity for cooperative leaders to develop and implement digital strategies that enhance financial literacy among members, thereby ensuring the resilience and competitiveness of cooperative enterprises in the digital era.